Paleoclimatic implications of an 850-year oxygen-isotope record from the northern Tibetan Plateau - Holmes, JA; Zhang, JW; Chen, FH; Qiang, MR (AMER GEOPHYSICAL UNION, 2007)
Oxygen-isotope records from the sediments of hydrologically-closed lakes are commonly interpreted in terms of changing effective precipitation. We compare an 850-year-long oxygen-isotope record derived from ostracode carbonate from the sediments of Sugan Lake, in the northern Tibetan Plateau, with tree-ring and ice core evidence for changing temperature, precipitation and isotopic composition of the lake's inflow. Taking into account all of these independent records, we show that variations in the carbonate delta O-18 values could not have been the result of varying effective precipitation alone: changes in water temperature and in the delta O-18 of source waters also played a significant role. Where independent records of temperature, precipitation or the isotopic composition of input waters are unavailable, care should be taken to avoid simplistic interpretations of carbonate stable isotope records, as these may contribute to incorrect paleoclimatic reconstructions.